Comparison of the skull of Brown Skua (Catharacta antarctica lonnbergi) and South Polar Skua (Catharacta maccormicki): differentiation source identification and discriminant analysis - Kass, Nicolás Ariel; Montalti, Diego; Hospitaleche, Carolina Acosta (2018)
Many contributions try to emphasize the similarities and differences between the Brown Skua Catharacta antarctica lonnbergi¸ and the South Polar Skua Catharacta maccormicki. Most of the morphological information of these species is based on field observation and referred to their external appearance. Few studies deal with their morphometry, mostly using characters measured in live birds, but the information about skeletal features is scarce. In the present study, skull differences between the Brown Skua and the South Polar Skua are quantified through independent quantitative analyses. Shape differences were evaluated in a geometric morphometrics test, while linear metric parameters were used to analyze the differences between species in a principal component analysis, and finally, in a discriminant test. Geometric morphometrics analysis cannot separate groups, whereas linear morphometrics divide well two different groups, showing significant differences. Notwithstanding, the most significant result was obtained using the discriminant analysis, which differentiates the species using simple equations which contain combined measures that can be easily obtained. Facultad de Ciencias Naturales y Museo